Ultra-wide beam scanning using a Conformal Transmit-array for Ka-band - Arraiano, A. (2019)
A conformal cylindrical transmit-array (TA) for ultra-wide mechanical beam steering is presented. The curved design allows to overcome the effective aperture size reduction caused by the beam tilt - intrinsic to all types of planar arrays. This design must also deal with the aberrations caused by feed displacement relative to the TA focus. Instead of using the usual unifocal approach, the TA phase correction was designed to have two pseudo-foci. In this way, the intrinsic phase error caused by feed displacement can be smeared among all beams improving the overall scanning performance of the antenna. The TA is composed of a collection of curved 5-layer stacked patches designed for the Ka-band uplink (30 GHz). The aperture has 215x143 mm in plane dimensions. The presented solution provides a 28.9 dBi maximum gain and scanning range up to 80º within 3.9 dB scan loss, which far exceeds the scanning performance of conventional planar TA.